(untitled) (Impetus, 2021)
In this text we reflect on the implications of living, the need to forge recognizable spaces to make life shared and enjoyable way. We begin with the quest to understand the act of living, some of its connotations and implementation of values to carry it out, as well as the identity configuration return this entails. Later we delve into the game, specifically soccer; the reason for its attraction as unblemished in all social spaces, the invitation to the enjoyment, adventure and integration that can offer its appeal to children and linking mainly while recognizing its negative characteristic of the human condition possibilities. Finally, living and soccertball together in the dimensions of tradition, myth, ritual and narration by the ability to reflect the moral life and express behaviors, this, especially from the perspective of MacIntyre, their ability to generate meetings on elements supposedly antagonistic.